Vision. drive. stamina : how Dell became the company with the power to do more - Swab, R. Gabrielle, (SAGE Knowledge. Cases., 2018)
This case takes the reader through the 30-year lifecycle of Dell Technologies, a company that has achieved wide success, but not without hiccups. Dell has continuously striven to use differentiation strategies to their competitive advantage. While Dell focused on the customer as the top priority, areas such as acquisitions, product diversification, Chief Executive Officer change, and choices made when Dell faced losing product quality and vision have determined the company's progress forward. The case highlights decisions behind the company's move from a publicly traded company to a privately-owned business.